1983
DOI: 10.2135/cropsci1983.0011183x002300050020x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tropical Environments in Breeding for Oil Composition of Soybean Genotypes Adapted to Temperate Climates1

Abstract: The objective of this study was to determine the influence of genotype X environment interaction on selection for fatty acid composition among soybean [Glycine max (L.) Merr.] lines adapted to the northern United States when grown in tropical environments. Twenty lines of maturity groups I to IIl were grown in three environments in Iowa and four environments in Puerto Rico. Seeds from two replications in each environment were analyzed for the percentages of palmitic, stearic, oleic, linoleic, and linolenic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Elevated stearic acid and low linolenic acid variants did not show stability for the trait in the M 3 generation, indicating the unstable nature of the trait across environments. This agrees well with the previous report by Hawkins et al [21] where the normal level of stearic acid was found to be relatively stable as compared to elevated levels across different environments. High oleic acid variants were comparatively stable.…”
Section: Stability Of Mutants In M 3 and M 4 Generationsupporting
confidence: 93%
“…Elevated stearic acid and low linolenic acid variants did not show stability for the trait in the M 3 generation, indicating the unstable nature of the trait across environments. This agrees well with the previous report by Hawkins et al [21] where the normal level of stearic acid was found to be relatively stable as compared to elevated levels across different environments. High oleic acid variants were comparatively stable.…”
Section: Stability Of Mutants In M 3 and M 4 Generationsupporting
confidence: 93%
“…This was because`Cutler71' showed higher stearic and lower linoleic acid composition in experiment 2, while`Clark', as well as`Aburamame' and`Tamamusume', showed stable fatty acid compositions. This indicates the presence of genotype±environment interaction on fatty acid composition, as reported by Burton et al (1983), Hawkins et al (1983), Cramer and ), and Carver et al (1986). In the present study, all the fatty acids showed dierent responses from each other to cropping season (Table 4).…”
Section: Discussionsupporting
confidence: 81%
“…There is a great intervarietal and interspeci®c variation for the fatty acid composition of soybean seeds, suggesting the possibility of genetic improvement of soybean seed oil quality (Hawkins et al 1983. Using genetic resources, breeders have successfully enhanced the oxidative stability of soybean seed oil by decreasing the polyunsaturated fatty acid content.…”
mentioning
confidence: 99%
“…Palmitate content can be evaluated effectively in a range of environments (Hawkins et al, 1983a, 1983b). Horesji et al (1994) found no significant genotype × environment interaction for palmitate content across three Iowa locations in 1 yr. Primomo et al (2002b) evaluated reduced and elevated palmitate lines during 3 yr at four locations in Canada.…”
Section: Palmitic Acid (Palmitate) (16:0)mentioning
confidence: 99%